2010
DOI: 10.1007/978-3-642-13708-2_11
|View full text |Cite
|
Sign up to set email alerts
|

Principles on the Security of AES against First and Second-Order Differential Power Analysis

Abstract: The Advanced Encryption Standard (AES) is a 128-bit block cipher that is currently being widely used in smartcards. Differential Power Analysis (DPA) is a powerful technique used to attack a cryptographic implementation in a resource-limited application environment like smartcards. Despite the extensive research on DPA of AES, it seems none has explicitly addressed the fundamental issue: How many rounds of the beginning and end parts of an AES implementation should be protected in order to resist practical DPA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 28 publications
0
15
0
Order By: Relevance
“…R RC [1] p c R RC [2] R RC [3] R RC [4] R RC [5] R RC [6] R RC [7] R RC [8] R RC [9] R RC [10] S M S -1 -1 -1 -1 -1 -1 1 2 3 4 5 6 7 8 9 Against DES software, previous attacks, such as those in [14], [15], and [16], have overcome some masking methods by fixing the inputs in a particular manner. Against an AES software implementation in which the inner rounds were not protected, Lu et al [17] demonstrated a first-and second-order differential power analysis (DPA) attack that exploits some inner round intermediate values by fixing certain parts of the inputs. Reparaz et al [18] demonstrated a chosen-input DPA attack in the third round of a DES software implementation.…”
Section: Preliminaries and Related Workmentioning
confidence: 99%
“…R RC [1] p c R RC [2] R RC [3] R RC [4] R RC [5] R RC [6] R RC [7] R RC [8] R RC [9] R RC [10] S M S -1 -1 -1 -1 -1 -1 1 2 3 4 5 6 7 8 9 Against DES software, previous attacks, such as those in [14], [15], and [16], have overcome some masking methods by fixing the inputs in a particular manner. Against an AES software implementation in which the inner rounds were not protected, Lu et al [17] demonstrated a first-and second-order differential power analysis (DPA) attack that exploits some inner round intermediate values by fixing certain parts of the inputs. Reparaz et al [18] demonstrated a chosen-input DPA attack in the third round of a DES software implementation.…”
Section: Preliminaries and Related Workmentioning
confidence: 99%
“…Although most of the published attacks against block cipher implementations are focused on the predictable [Standaert et al 2004] intermediate results in the outer rounds based on known plain-or cipher-text, recent results highlight the importance of considering leakages in the middle rounds as well. Work on techniques such as algebraic side-channel attacks (e.g., and ) and chosen message attacks [Lu et al 2010] has demonstrated the ability to directly target intermediate results in middle rounds of a cipher-in some cases even without any knowledge of the plain-or cipher-text.…”
Section: Leakage Mappingmentioning
confidence: 99%
“…The computation of modular exponentiation proceeds from the random starting point towards the MSB using the right-to-left binary exponentiation algorithm, returns to the starting point and then moves towards the LSB using the left-to-right binary exponentiation algorithm [29]. The authors in [30] presented a randomized window-scanning RSA scheme resistant to power analysis attacks, specifically to the CPA that uses different inputs to the same algorithm and analyze the power consumption traces. Even if the attacker was able to recover the bits, it will be difficult to put those key bits in the correct order.…”
Section: Side Channel Attacks: Differential Power Analysis Attack (Dpmentioning
confidence: 99%